Modeling of the Generalized Unified Power Flow Controller for Optimal Power Flow - Lubis, Rakhmad; Hadi, Sasongko Pramono; Tumiran, Tumiran (2011)
The latest generation of FACTS devices, the convertible static compensator (CSC) [1], is the progress of several innovative operating concepts in the historic development and application FACTS. One of the concepts is the GUPFC or multi-line UPFC have been done, which can control bus voltage and power flows of more than one line or according to even a sub-network. The GUPFC should have stronger control capability than the UPFC. In this paper it derived to pile up a novel concept of a mathematical model for the GUPFC consisting of one shunt converter and two or more series converters based on voltage source converter (VSCs) and DC link capacitor is developed and implemented in the nonlinear predictor-corrector primal-dual interior-point OPF algorithm. Numerical results with various GUPFC devices based on the IEEE 30 bus power system demonstrate the feasibility as well as the effectiveness of the GUPFC model established in the OPF method.